Effect of tillage, fertilizer and sorghum/desmodium intercrop cultivation on soils quality and yield of sorghum in an alfisol of a Northern Guinea Savanna of Nigeria - Chidowe, O.A.; Joshua, T.M.; Sunday, A.; Dawi, T.B.; Oluoch, M.; Zeyaur, K. (2014)
Soil quality protection under intensive land use and fast economic development has become a major challenge for sustainable resource use in the developing countries such as Nigeria. Conventional tillage practice is commonly practiced at land preparation and effect of this on soil quality for sustainable productivity was investigated in this study, in comparison with No Till, Conservation tillage, and split old ridge practices in combination with four nitrogen and three phosphorus fertilizer rates. Sorghum was the test crop. Results show that the soils were initially acid (pH 5.0 to 6.0), had low organic carbon (2.3 to 2.5gkg-1), total nitrogen (0.05gkg-1) and low to moderate available phosphorus (6.7 to 8.5mgkg-1) and needed restoration to support sustainable agricultural production. Tillage, sorghum/Desmodium and N and P fertilizer managements imposed showed that No Till practice (SDNT) sequestered significantly (P<0.05) higher organic carbon value (6.9 gkg-1), followed by Conservation tillage with incorporated and relayed D. Uncinatum (SDIC 5.8 gkg-1), Split old ridges with relayed D. uncinatum (SDOR 4.9gkg-1) and least, Conventional tillage (SC) without D. uncinatum (SC3.6 gkg-1).Total nitrogen content of the soils significantly improved under SDIC (0.17gkg-1 ), followed by SDOR (0.16gkg-1 ), SC (0.15gkg-1) and SDNT (0.13gkg-1) that were significantly different between treatments. Conservation tillage with incorporated and relayed D. uncinatum treatment (SDIC) resulted in significantly (P<0.05) higher (1.48tha-1) sorghum grain yield, followed by NoTill (SDNT) with D. uncinatum live mulch (1.32tha-1) that was significantly higher than yield under Split old ridges (1.20tha-1) with D. uncinatum live mulch (SDOR).Phosphorus fertilizer rates significantly enhanced stover yield, as 26.4 kgPha-1 rate resulted in the highest Stover yield (4.50tha-1) and the least (4.11 tha-1) from 13.2kgPha-1. Also, 50kgNha-1 significantly enhanced Stover yield of sorghum (4.83tha-1) greater than the other treatments. Conservation tillage practice therefore resulted in high sorghum grain yield (1.48 tha-1), attributed to improved soil quality conditions; optimum soil pH, available phosphorus, soil carbon and total nitrogen, that prevailed to support high sorghum grain yield. Soil quality (SQ) under the Conservation tillage practice (SDIC) was therefore rated SQ1 for being superior over other management practices evaluated.